2012
DOI: 10.1159/000339100
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in Geriatric Inhospital Patients: Effects on Results of a Comprehensive Geriatric Assessment

Abstract: Objectives: To study whether geriatric patients with mild-to-moderate hyponatremia (≤131 mmol/l) reveal different outcomes in structured tests for functional and cognitive impairments, depression and malnutrition compared to normonatremic patients. Design: Single-center, retrospective case control study. Setting: The study was conducted in a Geriatric Evaluation and Management Unit of a Department for Geriatrics and Internal Medicine. Methods and Participants: We included 2,880 elderly patients (75.6% female, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 67 publications
4
50
0
3
Order By: Relevance
“…Consequently, serum sodium measurements were missing in 56% of total patient-days in hospital. This same limitation has previously been encountered by various other groups and confirms concerns that clinical awareness of hyponatremia is low, predisposing already frail patients to worsened clinical outcomes [5, 27, 28]. Since patients did not have daily serum sodium measurements, it is likely that our report may underestimate the true incidence of hyponatremia in EPFF.…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, serum sodium measurements were missing in 56% of total patient-days in hospital. This same limitation has previously been encountered by various other groups and confirms concerns that clinical awareness of hyponatremia is low, predisposing already frail patients to worsened clinical outcomes [5, 27, 28]. Since patients did not have daily serum sodium measurements, it is likely that our report may underestimate the true incidence of hyponatremia in EPFF.…”
Section: Discussionsupporting
confidence: 74%
“…Renneboog et al found that patients with mild/moderate chronic 'asymptomatic' hyponatraemia present cognitive impairment upon testing, whereas the same patients with eunatraemia do not. 23 24 Gait instability is frequent in patients with mild/moderate hyponatraemia, and induces falls. In fact, 'asymptomatic' hyponatraemic patients were 67 times more likely to fall than normonatraemic controls in Renneboog's study.…”
Section: Clinical Manifestations Of Hyponatraemia In Older Peoplementioning
confidence: 99%
“…28 Mild hyponatraemia can induce marked anorexia and hyponatraemic patients on a geriatric ward present significantly lower mini-nutritional assessment scores than matched eunatraemic controls. 24 Non-correction of S Na for TP can also cause the frequency/severity of hyponatraemia to be underestimated. Correct evaluation of nutritional status is therefore essential, as are the detection and treatment of hyponatraemia in the malnourished elderly.…”
Section: Clinical Manifestations Of Hyponatraemia In Older Peoplementioning
confidence: 99%
“…These results underline the fact that hyponatremia with heart failure tends to afflict clinically frail older patients with malnutrition and neurological dysfunction [24][25][26]. Indeed, numerous hospital registries show that hyponatremia is associated to older age, the use of diuretics and an increasing comorbidity with conditions that predispose patients to the onset of this ion abnormality disorder (HF, cirrhosis, nephrotic syndrome, hypothyroidism, etc.)…”
Section: Discussionmentioning
confidence: 64%
“…This limitation makes it difficult to compare the results obtained with other HF registries. Regarding the type of hyponatremia, we have not been able to obtain variables associated with patients' degree of congestion (dilutional hyponatremia), NYHA functional classes, natriuretic peptide levels or hyponatremia treatment variables (particularly diuretics) [26,18]. The study design also did not allow us to differentiate between patients with HF who acquired hyponatremia during their hospital stay and those who already had chronic hyponatremia before the onset of decompensated heart failure.…”
Section: Discussionmentioning
confidence: 98%